SOCIAL ANXIETY, LIFELONG LEARNING TENDENCY AND ACADEMIC PERFORMANCE OF HIGH SCHOOL STUDENTS WITH PHYSICAL DISABILITIES - Santos, Jude (International Journal of Arts, Sciences and Education, 2023)
This study investigated the level and association between and among social anxiety, lifelong learning tendency and academic performance of high school students with physical disabilities (n=202) enrolled at the public secondary schools in the Division of Tuguegarao City, Cagayan Philippines. It employed descriptive correlational design and the variables were measured using standardized instruments. Results revealed that the students with physical disabilities generally experienced challenges related to social anxiety and lifelong learning. They struggle with social interactions, which can potentially affect their overall well-being and academic performance. Also, they face certain limitations that prevent them from fully engaging in lifelong learning activities. Notably, those who experience higher social anxiety tend to have poorer academic performance compared to their peers who have lower or do not have such anxiety. Additionally, those who are actively engaged in lifelong learning activities tend to show improved academic performance. Therefore, addressing social anxiety and promoting lifelong learning opportunities are indispensable in supporting the educational success of students with physical disabilities.